2017
DOI: 10.1038/srep40617
|View full text |Cite
|
Sign up to set email alerts
|

Nephro-toxic effects of intraperitoneally injected EGCG in diabetic mice: involvement of oxidative stress, inflammation and apoptosis

Abstract: Epigallocatechin gallate (EGCG) has been studied for its beneficial effects. However, some case reports have associated EGCG supplementation with hepato-toxicity. In the present study, we investigated the possible nephro-toxic effects of EGCG in diabetic mice. Streptozotocin (150 mg/kg, i.p.) was injected in mice for diabetes induction. EGCG (100 mg/kg/day, i.p.) was then given for 4 days. The administration of EGCG to diabetic mice caused 60% mortality with no death recorded in other groups. Blood samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…EGCG enhances cancer cell apoptosis [20,21]. It is also used for the prevention of cardiovascular diseases, especially atherosclerosis and coronary heart disease [17,22]. However, little is known about how EGCG ameliorates Ang II-induced oxidative stress and mitochondrial dysfunction in human endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG enhances cancer cell apoptosis [20,21]. It is also used for the prevention of cardiovascular diseases, especially atherosclerosis and coronary heart disease [17,22]. However, little is known about how EGCG ameliorates Ang II-induced oxidative stress and mitochondrial dysfunction in human endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…(−)-Epigallocatechin-3-gallate (EGCG), the major compound of green tea, has anti-inflammatory, antioxidative, and antiangiogenic effects both in vitro and in vivo [17,18,19]. EGCG enhances cancer cell apoptosis [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…is study revealed that EGCG has the potential to induce robust Caspase 3/7 activity. Recently, the Caspase 3 activity induced by EGCG treatments was also observed in bladder cancer cells SW780 [45] and chondrosarcoma cells [46], as well as in diabetic mice [47], indicating that EGCG plays a role in apoptosis via Caspase 3 activity. In general, polyphenols such as EGCG induced apoptosis in a caspasedependent manner [48][49][50].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have shown an association between DM and female reproductive disturbances, including amenorrhea, early menopause onset and infertility [ 2 , 6 , 9 , 10 , 12 18 ]. These alterations have been related to the injurious effects of hyperglycemia through the overproduction of AGEs and ROS, which trigger the caspase 3 apoptosis pathway [ 2 , 4 , 6 , 13 , 16 ]. However, these studies analyzed the effects of DM at a single time point, without correlating follicular loss with the expression of apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic metabolic disorder affecting more than 6% of the global population [ 1 ]. Chronically high glucose levels have deleterious effects on the structure and function of various organs [ 2 4 ]. Tissue damage has been related to the increased formation of advanced glycation end products (AGEs) [ 5 , 6 ] and the overproduction of reactive oxygen species (ROS) [ 2 , 5 ], which can cause oxidative stress, vascular endothelial cell damage and inflammatory cytokine production [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%